2013
DOI: 10.1027/1614-0001/a000098
|View full text |Cite
|
Sign up to set email alerts
|

If I Cry, Do You Care?

Abstract: Crying is a powerful solicitation of caregiving, yet little is known about the cognitive processes underpinning caring responses to crying others. This study examined (1) whether crying (compared to sad and happy) faces differentially elicited semantic activation of caregiving, and (2) whether individual differences in cognitive and emotional empathy moderated this activation. Ninety participants completed a lexical decision task in which caregiving, neutral, and nonwords were presented after subliminal exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Most existing research investigating the perception of emotional tearing uses posed facial expressions that feature artificial tears, added using eyedrops or digital enhancement (Reed et al, 2015;Ito et al, 2019). These artificial images have been used to explore how the presence of tears influences the perception of sadness (Hendriks et al, 2007;Ito et al, 2019), and the degree of helping behaviors elicited (Hendriks and Vingerhoets, 2006;Balsters et al, 2013;Lockwood et al, 2013). When images with visible tears are perceived as significantly sadder than the same image without tears, it is referred to as the tear effect (Provine et al, 2009).…”
Section: The Artificial Tearmentioning
confidence: 99%
See 4 more Smart Citations
“…Most existing research investigating the perception of emotional tearing uses posed facial expressions that feature artificial tears, added using eyedrops or digital enhancement (Reed et al, 2015;Ito et al, 2019). These artificial images have been used to explore how the presence of tears influences the perception of sadness (Hendriks et al, 2007;Ito et al, 2019), and the degree of helping behaviors elicited (Hendriks and Vingerhoets, 2006;Balsters et al, 2013;Lockwood et al, 2013). When images with visible tears are perceived as significantly sadder than the same image without tears, it is referred to as the tear effect (Provine et al, 2009).…”
Section: The Artificial Tearmentioning
confidence: 99%
“…In the context of our everyday lives, it is of interest to understand the relationship between tears, emotional support, and empathy. There is consensus that tears elicit greater emotional support and empathy compared to tear-free expressions (Hendriks and Vingerhoets, 2006;Balsters et al, 2013;Lockwood et al, 2013). Hendriks and Vingerhoets (2006) concluded that tearful expressions elicit greater support and reduced avoidance behaviors relative to other emotional displays.…”
Section: The Artificial Tearmentioning
confidence: 99%
See 3 more Smart Citations